Synergy of Polydopamine Nanovaccine and Endostar Alginate Hydrogel for Improving Antitumor Immune Responses Against Colon Tumor - Yang Y; Wang N; Tian XX; Wang X; Yang J; Leng XG; Zhang HL (International Journal of Nanomedicine, 2022)
Ying Yang,1 Ning Wang,2 XinXin Tian,1 XiaoLi Wang,1 Jing Yang,1 XiGang Leng,1 HaiLing Zhang1 1Institute of Biomedical Engineering, Chinese Academy of Medical Sciences & Peking Union Medical College, Tianjin Key Laboratory of Biomaterials, Tianjin, People’s Republic of China; 2Key Laboratory of Colloid and Interface Chemistry of the Ministry of Education, School of Chemistry and Chemical Engineering, Shandong University, Jinan, People’s Republic of ChinaCorrespondence: HaiLing Zhang, Institute of Biomedical Engineering, Chinese Academy of Medical Sciences & Peking Union Medical College, Tianjin Key Laboratory of Biomaterials, Tianjin, People’s Republic of China, Tel +86 22 8789 1191, Fax +86 22 8789 0153, Email zhanghl@bme.pumc.edu.cnBackground: Tumor immunotherapy, a novel type of therapeutic treatment, has a wide range of applications with potentially prolonged benefits. However, current immunotherapy has a low overall response rate in treating a variety of tumors. Combination of immunotherapy with other therapies can improve the therapeutic response rates. The purpose of this work was to explore the potential of anti-angiogenic treatment in combination with tumor cell lysate loaded polydopamine nanoparticle vaccine as a therapeutic strategy for colon tumor.Methods: We grafted tumor cell lysate onto polydopamine nanoparticles as nano-vaccine (TCLN) and fabricated alginate hydrogel loaded with Endostar (EH), then detected characteristics of EH and TCLN. We also estimated the cytotoxicity of EH/TCLN in vitro. In the tumor-bearing mouse model, we evaluated the antitumor effect of EH/TCLN treatment, and developed the animal survival study. After performing the EH/TCLN treatment, we also analyzed T cells and DCs using flow cytometry, and determined T cell responses and tumor microenvironmental cytokines. At last, we assessed the effect of the EH/TCLN treatment on anti-angiogenesis further.Results: When applied in combination with TCLN in MC-38 tumor-bearing mice, EH/TCLN significantly suppressed tumor growth with more than half of the mice showing tumor regression. In addition, EH/TCLN treatment resulted in noticeable changes in the tumor microenvironment. As compared with the control group, EH/TCLN treatment led to significantly reduced tumor angiogenesis and expression of tumor microenvironment-related cytokines (TMCs), increased proportion of CD8+ T cells in the spleen, lymph node and tumor, elevated activity of cytotoxic T lymphocytes (CTLs) and tumor cell apoptosis.Conclusion: The present study demonstrated that the EH/TCLN treatment effectively created a favorable immune microenvironment for the induction of antitumor immunity and improved antitumor immune responses.Graphical Abstract: Keywords: alginate, polydopamine, Endostar, colon tumor, angiogenesis, immunotherapy